Congenital anomalies prevalence in Addis Ababa and the Amhara region, Ethiopia: a descriptive cross-sectional study - Molla Taye; Mekbeb Afework; Wondwossen Fantaye; Ermias Diro; Alemayehu Worku (BMC, 2019)
Abstract Background During the first three months of pregnancy, the developing embryo may be susceptible to external and internal factors, which may lead to structural and functional congenital anomalies. The main objective of this study was to determine the prevalence of congenital anomalies in Addis Ababa and the Amhara region, Ethiopia. Methods A descriptive cross-sectional study was conducted on children 0-17 years of age who visited the 16 selected hospitals in Addis Ababa and the Amhara Region between January 1 and July 5, 2015. The proportions of neonates, infants, and children with external and internal congenital anomalies whether the anomalies were major or minor were estimated. Results Out of 76,201 children, 1518 of whom 57.6% were male identified with congenital anomalies. The overall proportion of congenital anomaly was 1.99% (95% CI: 1.89-2.091) i.e., 199 per 10,000 children. The proportion of neural tube defects, orofacial clefts, masculo-skeletal system anomalies, syndrome disorders, and cardiovascular system problems were 40.3% 37.7-43, 23.3% 21.3-25.4, 23.1% 20.9-25.2, 8% 6.7-9.4, and 2.6% 1.8-3.4, with a 95% CI, respectively. The majority (72.5%) of the mothers were multigravidae; 38(2.5%) of the mothers and 32(2.1%) of the fathers had history of other children with congenital anomalies. Similarly, 20(1.3%) of the participant children's mothers and 17(1.1%) of the fathers had familial history of congenital anomaly. Iron folate and multivitamin use by mothers during preconception and early pregnancy was found to be low. Conclusion Neural tube defects, orofacial clefts, and musculoskeletal anomalies were the observed prevalent problems. Maternal illness, viral infections, and malnutrition were seen in a significant number of the mothers. Iron folate/folic acid and multivitamin use by the mothers during and before pregnancy was very low.